2016
DOI: 10.1111/1365-2664.12786
|View full text |Cite
|
Sign up to set email alerts
|

Network analyses reveal intra‐ and interspecific differences in behaviour when passing a complex migration obstacle

Abstract: Summary Network theory offers new perspective on movement data by evaluating the relationships between animal movements (links) and detection locations (nodes) in spatially complex systems, including human‐altered landscapes. We applied network analyses to intra‐ and interspecific movement patterns in the migration behaviour and dam passage success of two anadromous fish species, Pacific lamprey Entosphenus tridentatus Gairdner and Chinook salmon Oncorhynchus tshawytscha Walbaum, when moving through a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…For example, passage probability may have decreased sharply if initial attempts to pass the barrier resulted in exhaustion in unsuccessful individuals. Unsuccessful attempts to pass also may have resulted in lamprey switching behavioural states (Gurarie et al., 2016) to search for alternative passage routes or spawning habitats (retreat) or adopt a sedentary sit‐and‐wait (for favourable passage conditions) strategy (Kirk & Caudill, 2017; Rooney et al., 2015). Although we show evidence of large‐scale exploratory behaviour, understanding these apparent sit‐and‐wait strategies requires finer‐scale telemetry/biologging studies to assess the behaviour of individuals that were delayed but remained in the immediate vicinity of migration barriers (Harbicht et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, passage probability may have decreased sharply if initial attempts to pass the barrier resulted in exhaustion in unsuccessful individuals. Unsuccessful attempts to pass also may have resulted in lamprey switching behavioural states (Gurarie et al., 2016) to search for alternative passage routes or spawning habitats (retreat) or adopt a sedentary sit‐and‐wait (for favourable passage conditions) strategy (Kirk & Caudill, 2017; Rooney et al., 2015). Although we show evidence of large‐scale exploratory behaviour, understanding these apparent sit‐and‐wait strategies requires finer‐scale telemetry/biologging studies to assess the behaviour of individuals that were delayed but remained in the immediate vicinity of migration barriers (Harbicht et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For example, at the first three weirs encountered by upstream-migrating lamprey, more than 30% of individuals made downstream (>1 km) movements, whereas others displayed a high degree of residency to the area immediately downstream of the barriers. This variation in movement tendency may reflect different strategies with respect to passage at barriers (Kirk & Caudill, 2017), with some individual lampreys searching for alternative routes and others awaiting favourable passage conditions. For example, the downstream extent of retreats from By testing the retreat rate data against abiotic data, we revealed that increased river discharge reduced retreat rates and the likelihood of exploratory behaviours, with this consistent with H2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we do not know much about the mechanisms causing differences in behavioral tendencies, behavioral differences could contribute to passage success or failure. Kirk and Caudill (2017) observed a wide range of behaviors in Pacific lampreys (Lampetra tridentate) at fishways in the Columbia River, Oregon, USA. Success at passing through the fishways was not related to body size but appeared related to behavioral differences as lampreys that failed to pass through the fishway made fewer entrance attempts and showed less milling behavior than lampreys that passed through the fishway.…”
Section: Intraspecific Variation In Physiology and Behaviormentioning
confidence: 99%